Riots without killings: policy learning in Amsterdam 1980-1985 - Rosenthal, Uriel (Contemporary crises, 1990)
From 1980 to 1985 serious clashes between police and squatter activists and their supporters occurred on the streets of Amsterdam. This paper describes the series of riots that took place and analyzes five of them in greater detail. Specifically, the investigation focuses on the issue of learning from recurrent crises. Did the authorities learn from one riot to the next? If so, in what ways and at what levels? And how effective did the lessons drawn prove to be - given the fact that the other party may have learned as well. Analyzing the key decisions that have been taken in these cases and confronting them with alternative scenarios that may have been pursued, suggests that learning from crises is a two-edged sword. Its potential benefits must be traded off against risks of overgeneralization or misapplication of lessons.The paper is commented on by Arthur H.W. Docters van Leeuwen, Head of the Dutch Security Service.